2018
DOI: 10.1071/rd17384
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine treatment of prepubertal male rats uniformly diminishes sex hormone levels and, in a subpopulation of animals, negatively affects sperm quality

Abstract: Fluoxetine (Flx) is a selective serotonin reuptake inhibitor that alters the male reproductive system when administered at the adult stage or after maternal exposure. In the present study we evaluated the effects of Flx administration on reproductive parameters during juvenile-peripubertal development when treated male rats reached adulthood. Groups of rats were treated daily with Flx (5mgkg-1, i.p.) or saline (0.9% NaCl), or were left untreated. Rats were treated between 30 and 53 days of age and were killed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…A previous study reported that fluoxetine administration decreased the luteinizing hormone and testosterone levels in intact rats ( Ayala et al, 2018 ). The present study showed that fluoxetine also diminished luteinizing hormone and testosterone levels in bulbectomized male rats.…”
Section: Discussionmentioning
confidence: 96%
“…A previous study reported that fluoxetine administration decreased the luteinizing hormone and testosterone levels in intact rats ( Ayala et al, 2018 ). The present study showed that fluoxetine also diminished luteinizing hormone and testosterone levels in bulbectomized male rats.…”
Section: Discussionmentioning
confidence: 96%
“…Oxidative stress is one of the main causes of male infertility since testicular germ cells are vulnerable to reactive oxygen species (ROS) and lipid peroxidation, 22,23 which increases cytotoxic aldehydes, as MDA, causing cellular dysfunction and death. 73,74 Moreover, the increase of RNS derived from the decomposition of NO impairs LC function and induces germ cell apoptosis. 23,25,75 Therefore, the high index of TUNEL positive-germ cells in the paroxetine-treated animals may also be related to ROS-and RNS-induced apoptosis.…”
Section: Paroxetine Changes Testicular Macrophages Population and Ind...mentioning
confidence: 99%